Climate impacts of retention forestry in a Swedish boreal pine forest. Issue 3 (4th May 2018) - Cherubini, Francesco; Santaniello, Francesca; Hu, Xiangping; Sonesson, Johan; Strømman, Anders Hammer; Weslien, Jan; Djupström, Line B.; Ranius, Thomas
ABSTRACT: The excessive simplification of forest structure associated with clear-cutting can carry risks for biodiversity. Tree retention is an alternative practice that maintains greater structural diversity, but its effects on climate change impacts relative to conventional harvesting are largely unexplored. By integrating field measurements from 12 forest stands with modelling approaches, we investigated the post-harvest effects on radiative forcing of tree retention in a Swedish boreal pine forest. In the near-term, impacts from carbon fluxes and surface albedo were of the same order of magnitude but with opposite sign (warming for carbon and cooling for albedo), with a net warming effect. In the long-term, the net effect turns to cooling, as the forest becomes a strong carbon sink. Retention had a significant effect on climate in the near-term, where differences between the various retention levels are more evident. At increasing tree retention, warming impacts from carbon fluxes tend to decrease, but cooling contributions from surface albedo are less pronounced. Balancing these effects, we find a net climate warming that increases with tree retention.